The vegetarian athlete's cookbook : more than 100 delicious recipes for active living - Bean, Anita (Bloomsbury, 2017)
The way we eat is changing. More and more of us are opting to eat fewer animal products or to cut them out entirely. Eating well to support a training regimen presents its own challenges, but as celebrated nutritionist Anita Bean shows, it is possible to eat delicious, healthy food and reach your athletic potential. Her new cookbook offers athletes--from weekend warriors to professionals--more than one hundred easy-to-prepare vegetarian and vegan recipes for breakfast, main meals, snacks, and more to allow the kind of performance every athlete aspires to, featuring gorgeous food photography and nutritional information for every recipe.